Antimicrobial susceptibility and risk factors of uropathogens in symptomatic urinary tract infection cases at Dessie Referral Hospital, Ethiopia - Destaw Kebede; Yeromnesh Shiferaw; Edosa Kebede; Wondmagegn Demsiss (BMC Microbiology)
Abstract Background Urinary tract infection (UTI) is one of the most common bacterial infections encountered by clinicians in developing countries, affecting the urethra, bladder, and kidneys. It is a prevalent infectious disease among outpatients and hospitalized patients, leading to morbidity and mortality. Antibiotic resistance among uropathogens varies geographically, but empirical treatment is common in our study area. Therefore, this study aimed to evaluate antimicrobial susceptibility and risk factors of uropathogens in symptomatic UTI cases at Dessie Referral Hospital in northeast Ethiopia. Methods A hospital-based cross-sectional study design was utilized to examine 256 participants with urinary tract complaints from February 1, 2024, to May 30, 2024. Consecutive convenience sampling was used to select participants. Midstream urine samples were collected, and bacteriological tests, including culture, Gram stain, biochemical tests, and antimicrobial susceptibility tests, were conducted following standard procedures. The data were entered into EpiData version 3.1 and analyzed using SPSS version 20 software. Bivariate and multivariate logistic regressions were carried out to identify potential risk factors associated with urinary tract infection. Results The overall prevalence of bacteriuria was 22.7%. Escherichia coli (E. coli) accounted for the highest proportion 21(30.4%), followed by Coagulase-negative Staphylococcus (CoNS) at 15(21.7%) and Klebsiella spp 12(17.4%). Most Gram-positive bacteria were susceptible to gentamicin 19(90.5%) but less sensitive to trimethoprim-sulfamethoxazole 16(76.2%) and nitrofurantoin 18(85.7%). High resistance rates were observed for penicillin 9(60%) and cefoxitin 14(66.7%). On the other hand, amikacin (83.3%), gentamicin (81.3%), and nitrofurantoin (89.7%) were effective against Gram-negative bacteria. Resistance to tetracycline and ampicillin was reported at 53.8% against both groups of bacteria. Female sex (AOR = 4.21; 95% CI = 1.43–8.29, P = 0.002), diabetes mellitus (AOR = 14.786; 95% CI = 3.91–70.72, P = 0.001), and human immunodeficiency virus positivity (AOR = 5.273; 95% CI = 2.596–17.410, P = 0.002) were identified as significant risk factors for bacteriuria. Conclusion The prevalence of UTI among syptomatic patients was 22.7%. E. coli and coagulase negative Staphylococcus were the predominant isolates. The identified bacteria were resistant to commonly use antimicrobials. Therefore, there should be continuous surveillance of UTI and antimicrobial susceptibility testing to minimize urinary tract infection and antibiotic resistance in our study setting.